Overexpression of Phosphate Transporter Gene CmPht1;2 Facilitated Pi Uptake and Alternated the Metabolic Profiles of Chrysanthemum Under Phosphate Deficiency - Liu, Chen; Su, Jiangshuo; Stephen, Githeng’u K.; Wang, Haibin; Song, Aiping; Chen, Fadi; Zhu, Yiyong; Chen, Sumei; Jiang, Jiafu (Frontiers in Plant Science, 2018)
Low availability of Phosphorus (P) in the soil is the principal limiting factor for the growth of cut chrysanthemum. Plant phosphate transporters (PTs) facilitate acquisition of inorganic phosphate (Pi) and its homeostasis within the plant. In the present study, CmPht1;2 of the Pht1 family was cloned from chrysanthemum. CmPht1;2 is composed of 12 transmembrane domains and localized to the plasma membrane. Expression of CmPht1;2 in roots was induced by Pi starvation. Chrysanthemum plants with overexpression of CmPht1;2 (Oe) showed higher Pi uptake, compared to the wild type (WT), both under Pi-starvation and Pi-sufficient conditions, and also showed higher root biomass compared to WT in the Pi-starvation conditions. Seven days after P-deficiency treatment, 85 distinct analytes were identified in the root and 27 in the shoots between Oe1 plant and WT. In which sophorose, sorbitol (sugars), hydroxybutyric acid (organic acids), and ornithine (amino acid) of CmPht1;2 overexpressing chrysanthemum are specific responses to P-starvation.